Increased ketone body oxidation provides additional energy for the failing heart without improving cardiac efficiency. Issue 11 (19th February 2019) - Ho, Kim L; Zhang, Liyan; Wagg, Cory; Al Batran, Rami; Gopal, Keshav; Levasseur, Jody; Leone, Teresa; Dyck, Jason R B; Ussher, John R; Muoio, Deborah M; Kelly, Daniel P; Lopaschuk, Gary D
Abstract: Aims: The failing heart is energy-starved and inefficient due to perturbations in energy metabolism. Although ketone oxidation has been shown recently to increase in the failing heart, it remains unknown whether this improves cardiac energy production or efficiency. We therefore assessed cardiac metabolism in failing hearts and determined whether increasing ketone oxidation improves cardiac energy production and efficiency. Methods and results: C57BL/6J mice underwent sham or transverse aortic constriction (TAC) surgery to induce pressure overload hypertrophy over 4-weeks. Isolated working hearts from these mice were perfused with radiolabelled β-hydroxybutyrate (βOHB), glucose, or palmitate to assess cardiac metabolism. Ejection fraction decreased by 45% in TAC mice. Failing hearts had decreased glucose oxidation while palmitate oxidation remained unchanged, resulting in a 35% decrease in energy production. Increasing βOHB levels from 0.2 to 0.6 mM increased ketone oxidation rates from 251 ± 24 to 834 ± 116 nmol·g dry wt −1 · min −1 in TAC hearts, rates which were significantly increased compared to sham hearts and occurred without decreasing glycolysis, glucose, or palmitate oxidation rates. Therefore, the contribution of ketones to energy production in TAC hearts increased to 18% and total energy production increased by 23%. Interestingly, glucose oxidation, in parallel with total ATP production, was also significantly upregulated in hearts upon increasing βOHB levels. However, while overall energy production increased, cardiac efficiency was not improved. Conclusions: Increasing ketone oxidation rates in failing hearts increases overall energy production without compromising glucose or fatty acid metabolism, albeit without increasing cardiac efficiency.